1989
DOI: 10.1111/j.1365-2125.1989.tb05434.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxytocin on basal and pethidine‐induced delayed gastric emptying.

Abstract: 1. Continuous infusion of oxytocin (0.33 u min‐1) accelerated gastric emptying of semisolid TC‐99m labelled Chelex‐100 resin/oatmeal in 10 healthy volunteers under basal conditions. 2. Administration of oxytocin did not change the pattern of gastric emptying delayed by pethidine. 3. The emptying pattern of semisolid has confirmed the existence of a lag phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 12 publications
1
38
0
3
Order By: Relevance
“…The presence of oxytocin in the myenteric plexus suggests an effect of oxytocin in enteric neurotransmission and could explain the effect of oxytocin on motility earlier observed, where intravenous infusion of oxytocin led to increased colonic peristalsis, and to accelerated gastric emptying of a meal in healthy women [3,4], whereas the oxytocin receptor antagonist delayed the gastric emptying [5]. Activated terminals of enteric motorneurons and smooth muscle cells form functional units that release transmitters and mediate and transduce neural inputs into mechanical responses [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of oxytocin in the myenteric plexus suggests an effect of oxytocin in enteric neurotransmission and could explain the effect of oxytocin on motility earlier observed, where intravenous infusion of oxytocin led to increased colonic peristalsis, and to accelerated gastric emptying of a meal in healthy women [3,4], whereas the oxytocin receptor antagonist delayed the gastric emptying [5]. Activated terminals of enteric motorneurons and smooth muscle cells form functional units that release transmitters and mediate and transduce neural inputs into mechanical responses [20].…”
Section: Discussionmentioning
confidence: 93%
“…Oxytocin is secreted into the blood in response to endogenous (after a fatty meal), and exogenous cholecystokinin (CCK) in women [1,2]. Intravenous infusion of oxytocin leads to increased colonic peristalsis, and to accelerated gastric emptying of a meal in healthy subjects [3,4], whereas an oxytocin receptor antagonist delays the gastric emptying [5]. In contrast, gastric motility is inhibited in dogs and rats [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous data have suggested that the effects of oxytocin on gastrointestinal motility are speciesdependent. For example, oxytocin accelerates (Hashmonai et al 1979;Petring 1989), and oxytocin receptor antagonists delay (Ohlsson et al 2006a) gastric emptying in humans, but oxytocin delays gastric emptying in rats (Wu et al 2002(Wu et al , 2003. The effects of oxytocin on the human stomach appear to be direct; however, the gastric effects of oxytocin in rats are blocked by cholecystokinin antagonists and thus are probably mediated indirectly by cholecystokinin.…”
Section: Introductionmentioning
confidence: 80%
“…Both OT and OT receptor (OTR) were expressed throughout the human gastrointestinal (GI) tract [6,10]. In rats, exogenous OT accelerated gastric and colonic motility in human, rabbits, and rats [3,9,12,13], inhibited the gastric emptying and intestinal transit in rats [20,21], and excited the phasic contraction of gallbladder in rabbits [4]. Most of these effects were abolished by atosiban, a specific OTR antagonist [3,4,21].…”
Section: Introductionmentioning
confidence: 99%